(untitled) (KULT_online, 2011)
Female academics with children have been the subject of gender studies research for years. In contrast, male professors with children—still the majority case—have scarcely been given a second glance, even though combining parenthood with the demands academia makes on its teachers is a big challenge not only for women. On the basis of biographical accounts of male professors with children, the present volume reflects on questions such as: How do men cope with the demands university makes on them? How do they act on the desiderata of their private environment? Is there a problem of balancing career and family roles for male academics, too? And if so, what does it look like in practice? As a result, these interviews show that for reasons of the structures of academic life, for men, too, managing everyday life as fathers and professors becomes a difficult balancing act. To this day, being active fathers and living a fulfilling family life seems not to be compatible with a professorship.